Business model innovation in the Finnish power electricity sector - Rabetino, Rodrigo; Kohtamäki, Marko; Rahman, Nayeem; Huikkola, Tuomas (IEEE, 2023)
The paper focuses on the patterns and nuances of business model innovation in the power electricity sector rather than its outcomes (e.g., specific business models). We conducted a multiple-case study involving three Finnish companies to scrutinize business model innovation within a changing industry disrupted by increasing digitalization and service-oriented opportunities. This study provides 16 shared routines and the related processes and practices for discovering (3 routines), generating (8 routines), and implementing (5 routines) new business models. In so doing, it contributes to the intersection of digital servitization and business model innovation literature.
Keywords: business model innovation; digitalization; digital servitization; power electricity sector; digitalisation; fi=Markkinointi|en=Marketing|; fi=Strateginen johtaminen|en=Strategic Management|